Experimental study of EUV mirror radiation damage resistance under long‐term free‐electron laser exposures below the single‐shot damage threshold. (22nd December 2017) - Makhotkin, Igor A.; Sobierajski, Ryszard; Chalupský, Jaromir; Tiedtke, Kai; de Vries, Gosse; Störmer, Michael; Scholze, Frank; Siewert, Frank; van de Kruijs, Robbert W. E.; Milov, Igor; Louis, Eric; Jacyna, Iwanna; et al.
Abstract : An experimental study of the durability of extreme UV optical coatings to a large number of free‐electron laser pulses is reported. Abstract : The durability of grazing‐ and normal‐incidence optical coatings has been experimentally assessed under free‐electron laser irradiation at various numbers of pulses up to 16 million shots and various fluence levels below 10% of the single‐shot damage threshold. The experiment was performed at FLASH, the Free‐electron LASer in Hamburg, using 13.5 nm extreme UV (EUV) radiation with 100 fs pulse duration. Polycrystalline ruthenium and amorphous carbon 50 nm thin films on silicon substrates were tested at total external reflection angles of 20° and 10° grazing incidence, respectively. Mo/Si periodical multilayer structures were tested in the Bragg reflection condition at 16° off‐normal angle of incidence. The exposed areas were analysed post‐mortem using differential contrast visible light microscopy, EUV reflectivity mapping and scanning X‐ray photoelectron spectroscopy. The analysis revealed that Ru and Mo/Si coatings exposed to the highest dose and fluence level show a few per cent drop in their EUV reflectivity, which is explained by EUV‐induced oxidation of the surface.